Playing for Change: Teens’ Attitudes Towards Climate Change Action as Expressed Through Interactive Digital Narrative Play - Skains, R. Lyle; Rudd, Jennifer A.; Horry, Ruth; Ross, Helen (Frontiers in Communication, 2022)
We designed and pilot tested “You and CO2”, a program designed to encourage students to reflect on their personal impact on the environment, while also appreciating their place within society to bring about positive societal change. Over three interlinked workshops, students analysed the carbon footprints of some everyday activities, which they then explored in more detail through interacting with a bespoke piece of interactive digital narrative (IDN), No World 4 Tomorrow. Previous papers have discussed the feasibility of the program and student engagement with the concepts. This paper presents analysis of the playthrough data as each participant in the program played the IDN to completion, examining trends in story selection choices for how they reflect students’ understandings and attitudes towards climate change and their own ability to make a difference in matters large and small pertaining to climate change.